MAGNETIC SUSCEPTIBILITY OF SOILS FROM UKRAINIAN CITIES AND EVALUATION OF POLLUTION LEVELS - Bondar, K.; Tsyupa, I.; Stakhiv, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper deals with comparative study of soil samples from 12 Ukrainian cities and one natural reserve by low-field and high-field magnetic  ) and its frequency dependence ( fd k ). The aim was to examine the data for the magnetic parameters mentioned above to evaluate ecological state of urban soils that accumulate particulate matter from industrial emissions. Low-field magnetic susceptibility of urban soils from Ukrainian cities is revealed to vary widely, namely from 2.3 to 7963.3×10-8 m3/ kg; its distribution overall showing the level of anthropogenic impact on the urban environment. Frequency dependence of the magnetic susceptibility of urban soils always has low values, for their being enriched with relatively large grains of magnetic minerals, contained in the exhaust gases from motor vehicles and industry. Polluted soils from industrial cities have predominantly high lf  and low fd k values. Conversely, unpolluted soils show the reverse dependence. Conclusively, Mariupol, Zaporizhia, Kryvyi Rih, cities of advanced metallurgical industry, top the list of the most polluted areas, while Boryspil, Ochakiv, Melitopol, cities of the lowest anthropogenic impact on the environment, lead the list of the least polluted areas.
Keywords: magnetic susceptibility; frequency dependence of the magnetic susceptibility; soil; city; industrial pollution